On the distribution of thermal fluxes at friction to some tribomechanical systems (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1995)
A general thermal problem at friction to some concrete tribomechanical systems is consideted in this paper. The temperature fields of these systems are found, on the base of which the distribution of thermal fluxes arisen at the friction is determined.